2015
DOI: 10.1080/10543406.2013.840646
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Methods for Treatment Selection in Seamless Phase II/III Clinical Trials Incorporating Information on Short-Term Endpoints

Abstract: In an adaptive seamless phase II/III clinical trial interim analysis, data are used for treatment selection, enabling resources to be focused on comparison of more effective treatment(s) with a control. In this paper, we compare two methods recently proposed to enable use of short-term endpoint data for decision-making at the interim analysis. The comparison focuses on the power and the probability of correctly identifying the most promising treatment. We show that the choice of method depends on how well shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…They show that the correlation between the measurements taken at different time points can be exploited in order to increase the precision of the estimate of the primary endpoint effect. Todd and Stallard (2005) describe a method for adaptive seamless phase II/III designs where a secondary endpoint is incorporated into the trial design in order to select the most promising treatment at an interim analysis (see also Stallard, 2010;Kunz et al, 2015). Furthermore, Kunz et al (2014) developed an approach to select the most promising treatment based on interim analysis data incorporating a short-term endpoint.…”
Section: Multiple Short-term Surrogate Endpointsmentioning
confidence: 99%
“…They show that the correlation between the measurements taken at different time points can be exploited in order to increase the precision of the estimate of the primary endpoint effect. Todd and Stallard (2005) describe a method for adaptive seamless phase II/III designs where a secondary endpoint is incorporated into the trial design in order to select the most promising treatment at an interim analysis (see also Stallard, 2010;Kunz et al, 2015). Furthermore, Kunz et al (2014) developed an approach to select the most promising treatment based on interim analysis data incorporating a short-term endpoint.…”
Section: Multiple Short-term Surrogate Endpointsmentioning
confidence: 99%
“…Similarly methods for continuous data have also been developed by Friede et al. (); Kunz, Friede, Parsons, Todd, and Stallard (); Stallard (); Stallard, Kunz, Todd, Parsons, and Friede () for Phase II/III seamless trials with treatment selection. Hampson and Jennison () discussed use of short‐term data in group sequential tests for delayed responses.…”
Section: Introductionmentioning
confidence: 99%
“…Their simulations have shown that all four approaches have good properties regarding the power and type I error in moderate to large sample sizes. Similar methods for continuous data have also been considered in the literatures . For example, Galbraith and Marschner adapted and extended the methodology described in the work of Marschner and Becker to include continuous endpoints assessed at an arbitrary number of follow‐up times.…”
Section: Introductionmentioning
confidence: 99%
“…Similar methods for continuous data have also been considered in the literatures. [15][16][17][18][19][20] For example, Galbraith and Marschner 15 adapted and extended the methodology described in the work of Marschner and Becker 9 to include continuous endpoints assessed at an arbitrary number of follow-up times. Hampson and Jennison 17 generalized this to a group sequential design for the situation where the primary endpoint is measured with delay.…”
Section: Introductionmentioning
confidence: 99%